Clinical Management of Arrhythmogenic Right Ventricular Cardiomyopathy: An Update - Migliore, Federico; Zorzi, Alessandro; Silvano, Maria; Rigato, Ilaria; Basso, Cristina; Thiene, Gaetano; Corrado, Domenico (Current Pharmaceutical Design, 2010)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetic heart muscle disease characterized by the peculiar right ventricular (RV) involvement. Distinctive pathologic features are myocardial atrophy and fibro-fatty replacement of the RV free wall, and clinical presentation is usually related to ventricular tachycardias with a left bundle branch block pattern or ventricular fibrillation leading to cardiac arrest, mostly in young people and athletes. Later in the disease evolution, progression and estension of RV muscle disease and left ventricular involvement may result in right or biventricular heart failure. In 1994 an International Task Force proposed standardized diagnostic criteria designed to guarantee an adequate specificity based on the presence of major and minor criteria encompassing electrocardiographic, arrhythmic, morphofunctional, histopathologic, and genetic factors; more recently, Task Force criteria have been modified to increase their diagnostic sensitivity. Retrospective analysis of clinical and pathologic series including fatal cases identified a series of risk factors such as malignant familial background, youthful age, previous syncope or cardiac arrest, competitive sport activity, severe RV disease with left ventricular involvement, and episodes of complex ventricular arrhythmias or ventricular tachycardia. The therapeutic options include beta blockers, antiarrhythmic drugs, catheter ablation, and implantable cardioverter defibrillator (ICD). The ICD is the most effective safe-guard against arrhythmic sudden death. In patients in whom ARVC has progressed to severe RV or biventricular systolic dysfunction with risk of thromboembolic complications, treatment consists of current therapy for heart failure including anticoagulant therapy. In case of refractory congestive heart failure, patients may become candidates for heart transplantation.
Keywords: catheter ablation